2021
DOI: 10.31539/bioedusains.v4i2.2414
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Komunitas Burung di Lahan Perkebunan Kopi dengan Naungan Pohon Alami

Abstract: This study aims to compare bird communities in coffee plantation habitats with tree shade systems in natural forests or trees planted by coffee farmers. The method used is the bird encounter rate per unit time. The results showed that the quantitative ecological values ​​of birds in two coffee plantation areas were Richness Indices (RI) = 11.18, Diversity Indices (DI) = 3.71, Sorensen Indices (SI) = 45.5% and the Similarity Index of Two Habitats (ISE) = 24.3%. As many as 65% of bird species in both coffee plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…The community's daily requirements, which are primarily met by farmers, rely heavily on agricultural goods, particularly the resources found in the nearby forests. Within the context of the economy, people in Petungkriyono villages gather non-timber forest products; for instance, residents of Kayupuring village tap sugar palm in natural forests (Fikri & Adinugraha, 2021); residents of several nearby villages, including Kasimpar village, Kayupuring (Wibowo et al, 2022;Widodo, 2021;Tanguay, 2020), tap pine resin from forests with limited production; and people harvest food items such as bamboo, fruit, cloves, coconut, and other vegetables (BPS Pekalongan Regency, 2023; Damayanti et al, 2018). The aforementioned activities are all direct advantages that the Petungkriyono people can obtain from the forests to meet their financial demands.…”
Section: The Sosiogeography Of Petungkriyonomentioning
confidence: 99%
“…The community's daily requirements, which are primarily met by farmers, rely heavily on agricultural goods, particularly the resources found in the nearby forests. Within the context of the economy, people in Petungkriyono villages gather non-timber forest products; for instance, residents of Kayupuring village tap sugar palm in natural forests (Fikri & Adinugraha, 2021); residents of several nearby villages, including Kasimpar village, Kayupuring (Wibowo et al, 2022;Widodo, 2021;Tanguay, 2020), tap pine resin from forests with limited production; and people harvest food items such as bamboo, fruit, cloves, coconut, and other vegetables (BPS Pekalongan Regency, 2023; Damayanti et al, 2018). The aforementioned activities are all direct advantages that the Petungkriyono people can obtain from the forests to meet their financial demands.…”
Section: The Sosiogeography Of Petungkriyonomentioning
confidence: 99%
“…Beberapa penelitian mengenai hewan yang telah dilakukan di Kebun Raya Cibinong adalah keragaman dan kelimpahan jenis kodok (Kurniati, 2010; Astuti dan Kurniati, 2010), serta pola distribusi dan dinamika komunitas burung (Widodo dan Sulistyadi, 2016). Sampai saat ini belum ada penelitian untuk mengetahui jenis-jenis kelelawar di Kebun Raya Cibinong.…”
Section: Pendahuluanunclassified
“…In contrast, mixed forests were found to have 24 bird species, with a population of 184 individuals. Moreover, it has been observed that birds have a predilection for inhabiting plantation environments [20]. According to a study conducted by [21], 25 avian species were documented inside the confines of the plantation region.…”
Section: Introductionmentioning
confidence: 99%